UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL KOOPERATIF TIPE STAD KELAS IX-5 SMP NEGERI 1 NAMORAMBE - Luter Karo-karo (Universitas Negeri Medan, 2016)
Abstract : Improving outcomes Learning Mathematics Through Cooperative Model Stad Type of Class IX-5 SMP Negeri 1 Namorambe. The subjects were students of class IX-5 SMP Negeri 1 Namorambe, in the academic year 2015/2016 amounted to 28 students. The results showed; (a) Data student activity cycle I and II writing, reading (42%) to (24%), working LKS (21%) to (45%), ask peers (11%) to (20%), asks teachers (9%) to (6%), and are not relevant to KBM (17%) to (5%). (b) The results of student learning cooperative learning model STAD first cycle the average - average 70.3 and the second cycle an average of 86 experienced an average increase of 15.7 mastery learning outcomes in the first cycle of 15 students or (51.72% ) and 26 students or (92.8%) this means increased from the first cycle to the second cycle of 41.08%. Keywords ; Learning Model STAD, Learning Outcomes, Learning Activities Abstrak : Upaya Peningkatan hasil Belajar Matematika Melalui Model Kooperatif Tipe Stad Kelas IX-5 SMP Negeri 1 Namorambe. Subjek penelitian adalah siswa kelas IX-5 SMP Negeri 1 Namorambe, Tahun Pelajaran 2015/2016 berjumlah 28 siswa. Hasil penelitian menunjukkan; (a) Data aktivitas siswa siklus I dan II menulis, membaca (42%) menjadi (24%), mengerjakan LKS (21%) menjadi (45%), bertanya sesama teman (11%) menjadi (20%), bertanya kepada guru (9%) menjadi (6%), dan yang tidak relevan dengan KBM (17%)menjadi (5%). (b) Hasil belajar siswa dengan model pembelajaran kooperatif tipe STAD siklus I rata – rata 70,3 dan siklus II rata-rata 86 mengalami peningkatan rata-rata 15,7 ketuntasan hasil belajar pada siklus I 15 orang siswa atau (51,72%) dan 26 orang siswa atau (92,8%) hal ini berarti meningkat dari siklus I ke Siklus II sebesar 41,08%. Kata Kunci ; Model Pembelajaran STAD, Hasil Belajar, Aktivitas Belajar